Material strength of long-term used penstock of a hydroelectric power plant. (December 2016) - Kawamura, F.; Miura, M.; Ebara, R.; Yanase, K.
Abstract: In this study, the material strength of a carbon steel (JIS SS400), which has been used for the penstock of a hydroelectric power plant for about 50 years, is examined. A series of data were obtained and analyzed by measuring the chemical compositions, observing the macro- and micro-structure and conducting tensile tests. The present study revealed that the material strength (0.2% proof strength and ultimate tensile strength) measured at one site can not be regarded as a reliable representative of the entire structure. On the other hand, strong and positive correlation between equivalent carbon content and material strength indicates that measuring the former is an effective and reasonably accurate estimate of the latter. In addition, potential use of nondestructive evaluations, including the Vickers hardness, and their reliability is discussed. In practice, a series of statistical analysis with those valuable field data provides us with the insight on the material strength of long-term used penstock.